Proteasome dysfunction in alveolar type 2 epithelial cells is associated with acute respiratory distress syndrome - Sneha Sitaraman (Nature Portfolio, 2019)
Abstract Proteasomes are a critical component of quality control that regulate turnover of short-lived, unfolded, and misfolded proteins. Proteasome activity has been therapeutically targeted and considered as a treatment option for several chronic lung disorders including pulmonary fibrosis. Although pharmacologic inhibition of proteasome activity effectively prevents the transformation of fibroblasts to myofibroblasts, the effect on alveolar type 2 (AT2) epithelial cells is not clear. To address this knowledge gap, we generated a genetic model in which a proteasome subunit, RPT3, which promotes assembly of active 26S proteasome, was conditionally deleted in AT2 cells of mice. Partial deletion of RPT3 resulted in 26S proteasome dysfunction, leading to augmented cell stress and cell death. Acute loss of AT2 cells resulted in depletion of alveolar surfactant, disruption of the alveolar epithelial barrier and, ultimately, lethal acute respiratory distress syndrome (ARDS). This study underscores importance of proteasome function in maintenance of AT2 cell homeostasis and supports the need to further investigate the role of proteasome dysfunction in ARDS pathogenesis.